2020
DOI: 10.1016/j.jsg.2020.104064
|View full text |Cite
|
Sign up to set email alerts
|

Strain patterns in glacitectonically thrusted sediments and conditions during thrusting

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Deformation associated with transport is focused along thin, water-lubricated zones, often allowing thrust blocks of non-or weakly lithified and unfrozen sediment to move with only limited internal deformation [29,54]. Thrust stacks record repeated events of thrusting, hydrofracturing, and water-escape [58]. The initial detachment of soft sediment blocks in ice marginal zones took place in response to ice-push and gravity-spreading at the margins of retreating glaciers in Iceland [56], Denmark [58], and Sweden [59].…”
Section: Glacial Ripping and Rubble Till Formation In Other Sedimentary Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Deformation associated with transport is focused along thin, water-lubricated zones, often allowing thrust blocks of non-or weakly lithified and unfrozen sediment to move with only limited internal deformation [29,54]. Thrust stacks record repeated events of thrusting, hydrofracturing, and water-escape [58]. The initial detachment of soft sediment blocks in ice marginal zones took place in response to ice-push and gravity-spreading at the margins of retreating glaciers in Iceland [56], Denmark [58], and Sweden [59].…”
Section: Glacial Ripping and Rubble Till Formation In Other Sedimentary Rocksmentioning
confidence: 99%
“…Thrust stacks record repeated events of thrusting, hydrofracturing, and water-escape [58]. The initial detachment of soft sediment blocks in ice marginal zones took place in response to ice-push and gravity-spreading at the margins of retreating glaciers in Iceland [56], Denmark [58], and Sweden [59]. Beneath the retreating ice margin at Loch Eriboll, glaciological conditions were broadly similar, with high meltwater fluxes, episodically high groundwater pressure, and thin ice cover.…”
Section: Glacial Ripping and Rubble Till Formation In Other Sedimentary Rocksmentioning
confidence: 99%
“…Deformation associated with transport is focused along thin, water-lubricated zones, often allowing thrust blocks of non-or weakly lithified and unfrozen sediment to move with only limited internal deformation [55] [30]. Thrust stacks record repeated events of thrusting, hydrofracturing and water-escape [59]. The initial detachment of soft sediment blocks in ice marginal zones took place in response of ice-push and gravity-spreading at the margins of retreating glaciers in Iceland [57], Denmark [59] and Sweden [60].…”
Section: Glacial Ripping and Rubble Till Formation In Other Sedimentary Rocksmentioning
confidence: 99%
“…Thrust stacks record repeated events of thrusting, hydrofracturing and water-escape [59]. The initial detachment of soft sediment blocks in ice marginal zones took place in response of ice-push and gravity-spreading at the margins of retreating glaciers in Iceland [57], Denmark [59] and Sweden [60]. Beneath the retreating ice margin at Loch Eriboll, glaciological conditions were broadly similar, with high meltwater fluxes, episodically high groundwater pressure and thin ice cover.…”
Section: Glacial Ripping and Rubble Till Formation In Other Sedimentary Rocksmentioning
confidence: 99%
“…Using compressive strength tests on ice from Taylor Glacier Lawson (1996) showed that the addition of 10% debris by volume resulted in increases and decreases in ice viscosity. Although some studies have concluded that the addition of debris has no impact on the strength of the ice (Cuffey et al., 2000; Jacka et al., 2003; Moore, 2014), the general view is that ice containing sediment is expected to be stronger than adjacent ice and less susceptible to ductile deformation well below the freezing point (Moore, 2014; Warbritton et al., 2020). In an extensive review of the behavior of frozen debris Moore (2014) concluded that ice‐debris mixtures are more resistant to deformation at low temperatures than pure ice but that at temperatures closer to melting the growth of an interfacial water film can lead to profound weakening.…”
Section: Introductionmentioning
confidence: 99%